Students' Instagram Social Media Behavior A Study at Aisyiyah Boarding School, Indonesia - ., Yulianti; W. Cholifah, Yuristia; Muthiah Umar, Tia; Lilis Chaerowati, Dede (KnE Social Sciences, 2023)
There has been studies on social media use in Asia, especially in Indonesia. However, not many of them exclusively emphasize on one particular homogeneous community based on religion aspect. This paper aims to describe the use of Instagram among muslimah students in an Islamic Boarding School in West Java, Indonesia. Specifically, this study portrays how muslimah students use and behave during their time using Instagram. This paper also tries to display their understanding on the emergence of safety and security setting function. The data were taken from online questionnaires shared to muslimah students at Aisyiyah Boarding School. The questions are open and closed questions. The research method used is a descriptive quantitative method. The results show that their social media behaviors are positively formed in an environment that supports well-scheduled activities. They only use Instagram occasionally, especially when the teachers ask them to submit tasks there. They rarely post personal contents that have no correlation with school assignments. Most of them use the “block comments and users” setting to keep their account private and safe. They claimed themselves as a non-Instagram addicts as they never experience the same fun feeling when they socialize face-to-face with their friends. Keywords: social media study, Muslimah students, Instagram users behavior